HIASAN DINDING DENGAN OBJEK BUNGA TERATAI MELALUI TEKNIK SULAM PITA DAN BORDIR - WINDIA MINSUNDARI, Drs. Erwin A, M.Sn., Yofita Sandra, S.Pd., M.Pd. (Serupa The Journal of Art Education, 2018)
Lotus flower are aquatic plants that live in swamps or pons. Lotus flowers mostly grow in muddy and dirty water, so the lotus flowers can grow well without being affected by the surrounding environment. The uniqueness and beauty of the lotus flower is very interesting to be used as an inspiration in creating artwork that is embroidered ribbon and embroidery techniques.This creation of works aims to visualize the beauty of the lotua flower. The technique used in ribbon embroidery using sewing machine techniques. After performing a series of long creation process, then creates 10 embroidered ribbon with titles : 1) Spirit, 2) Life journey, 3) Independence, 4) Compete, 5) Survive, 6) Never Give Up, 7) Allgiance, 8) End Story, 9) Leaders, 10) Together. These embroidery and embroidered works should be a good economic value and business opportunity.Keywords : Lotus, Embroidered Ribbon and Embroidery.